Fabrication of Silk-Hyaluronan Composite as a Potential Scaffold for Tissue Repair - Yu, Li-Min; Liu, Tao; Ma, Yu-Long; Zhang, Feng; Huang, Yong-Can; Fan, Zhi-Hai (Frontiers in Bioengineering and Biotechnology, 2020)
Interest is rapid growing in the design and preparation of bioactive scaffolds mimicking the biochemical composition and physical microstructure for tissue repair. In this study, a biomimetic biomaterial with nanofibrous architecture composed of silk fibroin and hyaluronic acid (HA) was prepared. Silk fibroin nanofiber was firstly assembled in water and then used as the nanostructural cue; after blending with hyaluronan (silk:HA=10:1) and the process of freeze-drying, the resulting composite scaffolds exhibited desirable 3D porous structure and specific nanofiber features. These scaffolds were very porous with the porosity up to 99%. The mean compressive modulus of silk-HA scaffolds with HA MW of 0.6, 1.6 and 2.6 ×106 Da was about 28.3, 30.2, and 29.8 kPa respectively; all these values were much higher than that of pure silk scaffold (27.5kPa). This scaffold showed good biocompatibility with bone marrow mesenchymal stem cells and it enhanced the cellular proliferation significantly when compared with the plain silk fibroin. Collectively, the silk-hyaluronan composite scaffold with nanofibrous structure and good biocompatibility was successfully prepared, which deserved further exploration as biomimetic platform for mesenchymal stem cell-based therapy for tissue repair.